Development of admixed lubricant for warm die and warm compaction of high-density Pm iron - Oh, Min Chul; Ahn, Byungmin (Archives of Metallurgy and Materials, 2021)
The objective of the present research is to develop new admixed lubricants which can be used for high-density sintered iron when processed using warm die and warm compaction. Depending on various lubricants, the effect of compaction temperature on the ejection behavior and sintered properties was studied. Lubricants were prepared by mixing of Zn-stearate and ethylene bis stearamide (EBS) in various compositions. The iron powders blended with lubricants were compacted under the pressure of 700 MPa at various temperatures. The green compacts were sintered at 1120°C for 30 min. Microstructure, density, hardness, and transverse rupture strength of sintered materials with different lubricants were investigated in detail.
Keywords: Compaction temperature; Ethylene bis-stearamide (EBS); Green compacts; Sintered iron; Sintered materials; Transverse rupture strength; Warm compaction; Ejection pressure; Lubricants; Powder metallurgy; Warm compaction; Warm die